Expression of the cystic fibrosis transmembrane conductance regulator gene in the respiratory tract of normal individuals and individuals with cystic fibrosis. - Trapnell, B C (1991)
The most common mutation of the cystic fibrosis transmembrane conductance regulator gene, CFTR, associated with the clinical disorder cystic fibrosis (CF) is called "delta Phe508," a triple-base deletion resulting in loss of phenylalanine at residue 508 of the predicted 1480-amino acid CFTR protein. In the context that the lung is the major site of morbidity and mortality in CF, we evaluated airway epithelial cells for CFTR mRNA transcripts in normal individuals, normal-delta Phe508 heterozygotes, and delta Phe508 homozygotes to determine if the normal and delta Phe508 CFTR alleles are expressed in the respiratory epithelium, to what extent they are expressed, and whether there are relative differences in the expression of the normal and abnormal alleles at the mRNA level. Respiratory tract epithelial cells recovered by fiberoptic bronchoscopy with a cytology brush demonstrated CFTR mRNA transcripts with sequences appropriately reflecting the normal and delta Phe508 CFTR alleles of the various study groups. CFTR gene expression quantified by limited polymerase chain reaction amplification showed that in normal individuals, CFTR mRNA transcripts are expressed in nasal, tracheal, and bronchial epithelial cells at approximately 1-2 copies per cell, more than 100-fold greater than in pharyngeal epithelium. Importantly, allele-specific hybridization studies demonstrated that the normal and delta Phe508 CFTR alleles are expressed in the respiratory epithelium in similar amounts.